Host responses which control Trypanosoma brucei parasites - Black, Samuel J. (Cambridge University Press, 1986)
Two host responses control Trypanosoma brucei parasitaemia in mice: an immune system-independent process which regulates the rate of parasite multiplication, and an antibody response specific for external epitopes...on parasite-attached variable surface glycoprotein (VSG), which determines the rate of parasite destruction. Parasite multiplication appears to be stimulated by host-derived growth factors which have a molecular mass of 105 to greater than 106 daltons. These molecules are not lipoproteins or immunoglobulins and serve to maintain T. brucei parasites as dividing slender forms. When the molecules become limiting, the parasites differentiate to nondividing stumpy forms. Nondividing stumpy-form T. brucei parasites degenerate in their mammalian host, giving rise to fragments which stimulate antibody responses. In the absence of these immunostimulatory fragments, no antibody responses are induced, i.e. antibody responses in animals infected with the parasites is modified by an immunodepressive reaction. Immunodepression is associated with rapid disruption of splenic organization into red and white pulp areas, and the generation of plasma cells which have highly distended sacs of endoplasmic reticulum and do not secrete antibody. The information on which these conclusions are based is reviewed and the relevance of the studies to the Development of strategies for the control of African trypanosomes in their mammalian hosts is discussed. The information on which these conclusions are based is reviewed and the relevance of the studies to the Development of strategies for the control of African trypanosomes in their mammalian hosts is discussed.